Construction Grammar Approach to Teaching ESL Writing in China - Bing, Zhao (Journal of International Studies, Prince of Songkla University, 2014)
The major problems in Chinese students’ ESL writing comprise lexical misuse, grammatical mistakes, collocational errors, lack of consistency, logic and idiomaticity. The past studies mainly focus on the implications and application of construction grammar to ESL acquisition and teaching as a whole, without pertinence to ESL writing in China. The current research aims to clarify the relation between construction and lexical chunks and specifically explore the applicable means of construction grammar approach to teaching ESL writing in China.